Revision of the genus Mniophila Stephens, 1831 (Coleoptera: Chrysomelidae). - Nadein, Konstantin S. (Contributions to Entomology = Beiträge zur Entomologie, 2009)
A revision of the genus Mniophila Stephens, 1831 is provided. Redescriptions of the genus and species, differential diagnoses, and distribution are given. New data on biology are presented. Three new species: Mniophila caucasica sp. n. from Caucasus (Russia, Abkhazia, Georgia, Azerbaijan), Mniophila transcaucasica sp. n. from Armenia and Georgia, and Mniophila taurica sp. n. from Crimea are described. The species level status of Mniophila bosnica Apfelbeck, 1914 is confirmed. The status of Mniophila muscorum turcica L. Medvedev, 1970 is elevated to a species level. The generic position of Mniophila exulans Samuelson, 1973 is discussed.KeywordsColeoptera, Chrysomelidae, Alticini, Mniophila, revision, description, distribution, new species.Nomenclatural Actscaucasica Nadein, 2009 (Mniophila), spec. n.taurica Nadein, 2009 (Mniophila), spec. n.transcaucasica Nadein, 2009 (Mniophila), spec. n.turcica L. Medvedev, 1970 (Mniophila), stat. rev. hitherto Mniophila muscorum turcica